The Role of Gut and Oral Microbiota in the Formation and Rupture of Intracranial Aneurysms: A Literature Review. - Joerger, Ann Kathrin; Albrecht, Carolin; Rothhammer, Veit; Neuhaus, Klaus; Wagner, Arthur; Meyer, Bernhard; Wostrack, Maria (International Journal of Molecular Sciences, 2023)
In recent years, there has been a growing interest in the role of the microbiome in cardiovascular and cerebrovascular diseases. Emerging research highlights the potential role of the microbiome in intracranial aneurysm (IA) formation and rupture, particularly in relation to inflammation. In this review, we aim to explore the existing literature regarding the influence of the gut and oral microbiome on IA formation and rupture. In the first section, we provide background information, elucidating the connection between inflammation and aneurysm formation and presenting potential mechanisms of gut-brain interaction. Additionally, we explain the methods for microbiome analysis. The second section reviews existing studies that investigate the relationship between the gut and oral microbiome and IAs. We conclude with a prospective overview, highlighting the extent to which the microbiome is already therapeutically utilized in other fields. Furthermore, we address the challenges associated with the context of IAs that still need to be overcome.
EVALuna2:552389